2014
DOI: 10.1242/dmm.016873
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning drugs for inflammatory disease-fishing for new anti-inflammatory agents

Abstract: Inflammation is an important and appropriate host response to infection or injury. However, dysregulation of this response, with resulting persistent or inappropriate inflammation, underlies a broad range of pathological processes, from inflammatory dermatoses to type 2 diabetes and cancer. As such, identifying new drugs to suppress inflammation is an area of intense interest. Despite notable successes, there still exists an unmet need for new effective therapeutic approaches to treat inflammation. Traditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 60 publications
0
34
0
Order By: Relevance
“…Prof. Crosier's lab screened another 153 potential anti-inflammatory drugs screened by zebrafish a in vivo neutrophil migration assay (D153, Table S1) 16 . The two sets of drugs (D101 and D153) were used to evaluate the predictions of network-based screening approach in this work.…”
Section: Network-based Drug Screening and Repositioningmentioning
confidence: 99%
See 2 more Smart Citations
“…Prof. Crosier's lab screened another 153 potential anti-inflammatory drugs screened by zebrafish a in vivo neutrophil migration assay (D153, Table S1) 16 . The two sets of drugs (D101 and D153) were used to evaluate the predictions of network-based screening approach in this work.…”
Section: Network-based Drug Screening and Repositioningmentioning
confidence: 99%
“…The two sets of drugs (D101 and D153) were used to evaluate the predictions of network-based screening approach in this work. Prof. Crosier's work also revealed that many drugs had anti-inflammatory activities though they were not approved as anti-inflammatory drugs 16 . However, the zebrafish in vivo neutrophil migration assay determined the ability of a drug to suppress the recruitment of neutrophils to tail fin injury, not general anti-inflammatory activity.…”
Section: Network-based Drug Screening and Repositioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Highlighting how the zebrafish can accelerate drug discovery, a drug originally identified to enhance blood stem cell numbers in embryonic zebrafish has progressed to phase 1b clinical trials in only 5 years [51][52][53][54] . In support of this approach as a strategy to identify new drugs to treat skin inflammation, we recently performed a zebra fish drug screen where we uncovered previously unappreciated antiinflammatory activities for drugs that demonstrated conserved activity in a murine model of skin inflammation [55] . Our work has highlighted the potential to live image elevated mitochondrial uptake of fluorescent FAs and mROS production within epidermal cells during inflammation [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Several chemical screens that aim to identify anti‐inflammatory compounds, using the presence of fluorescent neutrophils at injury sites as readouts, are performed in zebrafish. Several screens are performed in a self‐resolving inflammation model induced by tail amputation . A more streamlined approach that allows an increased degree of automation has been achieved with a chemically induced inflammation method, inflicted by transient copper sulfate treatment that selectively induces hair cell death in the lateral line system that results in rapid granulocyte recruitment .…”
Section: Zebrafish Models To Study Neutrophil Biologymentioning
confidence: 99%